The implementation of persuasive technology principles in mobile application development: a qualitative study - Shafin, Noor Afifah (2017)
Preceding studies of persuasive technology have mentioned several benefits on the implementation of persuasive design features of the Persuasive System Design (PSD) model such as creating users' engagement and acceptance and continuous usage. However, available literatures have not sufficiently address the implementation of these design principles particularly in the context of mobile application development as compared to system development. Furthermore, there are low numbers of discussion that have relate the implementation of these design principles towards the achievement of the persuasive system developed. Hence, this study was conducted to qualitatively explore the way persuasive design principles were implemented as well as the mobile application development process followed in three different levels of mobile applications' attainments. Within this study, seven semi-structured interviews were conducted with the involvement of fifteen (15) Android mobile applications in the area of utilities category. These mobile applications were then categorized into successful, partially successful and less successful categories based on their numbers of mobile application downloaded for three consecutive years which is from 2013 until 2015. The results from the content analysis conducted have shown that the mobile applications of the successful category have implemented a lot more persuasive design principles as compared to the other two categories. Moreover, it is also found that all of the mobile applications of the category had follow a more detailed process of mobile application development with the emphasizing on product introduction to the users. A model of the implementation of persuasive design principles in mobile application development was then proposed based on the findings gained from this research. The results from this study have provided contribution to the body of knowledge by leveraging the domain of persuasive technology studies particularly in mobile application development.